Engrailed 1 mediates correct formation of limb innervation through two distinct mechanisms. - Rosa-Eva Huettl; Georg Luxenhofer; Elisa Bianchi; Corinna Haupt; Rajiv Joshi; Alain Prochiantz; Andrea B Huber (PLoS ONE)
Engrailed-1 (En1) is expressed in the ventral ectoderm of the developing limb where it plays an instructive role in the dorsal-ventral patterning of the forelimb. Besides its well-described role as a transcription factor in regulating gene expression through its DNA-binding domain, En1 may also be secreted to form an extracellular gradient, and directly impact on the formation of the retinotectal map. We show here that absence of En1 causes mispatterning of the forelimb and thus defects in the dorsal-ventral pathfinding choice of motor axons in vivo. In addition, En1 but not En2 also has a direct and specific repulsive effect on motor axons of the lateral aspect of the lateral motor column (LMC) but not on medial LMC projections. Moreover, an ectopic dorsal source of En1 pushes lateral LMC axons to the ventral limb in vivo. Thus, En1 controls the establishment of limb innervation through two distinct molecular mechanisms.